Multimetallic microparticles increase the potency of rifampicin against intracellular Mycobacterium tuberculosis - Ellis,T; Chiappi,M; García-Trenco,A; Al-Ejji,M; Sarkar,S; Georgiou,TK; Shaffer,MSP; Tetley,TD; Schwander,S; Ryan,MP; Porter,AE (ACS Nano, 2018)
Mycobacterium tuberculosis ( M.tb) has the extraordinary ability to adapt to the administration of antibiotics through the development of resistance mechanisms. By rapidly exporting drugs from within the cytosol, these pathogenic bacteria diminish antibiotic potency and drive the presentation of drug-tolerant tuberculosis (TB). The membrane integrity of M.tb is pivotal in retaining these drug-resistant traits. Silver (Ag) and zinc oxide (ZnO) nanoparticles (NPs) are established antimicrobial agents that effectively compromise membrane stability, giving rise to increased bacterial permeability to antibiotics. In this work, biodegradable multimetallic microparticles (MMPs), containing Ag NPs and ZnO NPs, were developed for use in pulmonary delivery of antituberculous drugs to the endosomal system of M.tb-infected macrophages. Efficient uptake of MMPs by M.tb-infected THP1 cells was demonstrated using an in vitro macrophage infection model, with direct interaction between MMPs and M.tb visualized with the use of electron FIB-SEM tomography. The release of Ag NPs and ZnO NPs within the macrophage endosomal system increased the potency of the model antibiotic rifampicin by as much as 76%, realized through an increase in membrane disorder of intracellular M.tb. MMPs were effective at independently driving membrane destruction of extracellular bacilli located at the exterior face of THP1 macrophages. This MMP system presents as an effective drug delivery vehicle that could be used for the transport of antituberculous drugs such as rifampicin to infected alveolar macrophages, while increasing drug potency. By increasing M.tb membrane permeability, such a system may prove effectual in improving treatment of drug-susceptible TB in addition to M.tb strains considered drug-resistant.